Personal Pronouns in Yakkha: A Comparative Study - Shrestha, Kusum (Kirat Pragya किरात प्रज्ञा, 2026)
This paper compares the personal and possessive pronoun systems of two varieties of the Yakkha language—Marek Yakkha (MY) and Tumok Yakkha (TY)—both belonging to the Greater Eastern Kiranti branch of Sino-Tibetan. The analysis draws on primary elicited data from native speakers of Marek Yakkha and on secondary data from Schackow (2015) for Tumok Yakkha. The study shows that while both varieties share core Kiranti features such as a three-way number distinction (singular, dual, and plural) and nonsingular marking through , they differ significantly in clusivity marking, phonological shape, and morphological elaboration. Marek Yakkha preserves a fuller distinction between dual inclusive and exclusive forms, whereas Tumok Yakkha neutralizes this contrast. In the possessive domain, both varieties show irregular paradigms distinct from their personal pronouns and employ the genitive clitic=ga, but they diverge in prefixal patterns and form complexity. Overall, the findings provide evidence that Marek Yakkha constitutes a distinct linguistic variety within the Yakkha cluster, reflecting both shared inheritance and independent developments.